2023
DOI: 10.1093/infdis/jiad111
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Coronavirus Disease 2019 Vaccine Antibody Responses to Omicron Variants Suggest That Responses to Divergent Variants Would Be Improved With Matched Vaccine Antigens

Abstract: We compared neutralizing antibody responses to BA.4/5, BQ.1.1, XBB, and XBB.1.5 Omicron SARS-CoV-2 variants after a bivalent or ancestral COVID-19 mRNA booster vaccine or post-vaccination infection. We found that the bivalent booster elicited moderately high antibody titers against BA.4/5 that were approximately two-fold higher against all Omicron variants than titers elicited by the monovalent booster. The bivalent booster elicited low but similar titers against both XBB and XBB.1.5 variants. These findings i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…All data of V3 sera, except neutralizations against the stains of XBB-lineages, were reported previously 26 . Neutralization titers against D614G, BA.4/BA.5, BQ.1.1, XBB and XBB1.5 in the sera panels of V4+Bi, V3+Bi, V3+PVI and V4 were reported previously 29 . XBB.1.5 booster group* includes: six individuals without reported PVIs; three individuals with presumed BA.1 PVIs; four individuals with presumed BA.5 PVIs after three doses of the ancestral COVID-19 vaccine; and three individuals with presumed XBB PVIs after the bivalent booster.…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…All data of V3 sera, except neutralizations against the stains of XBB-lineages, were reported previously 26 . Neutralization titers against D614G, BA.4/BA.5, BQ.1.1, XBB and XBB1.5 in the sera panels of V4+Bi, V3+Bi, V3+PVI and V4 were reported previously 29 . XBB.1.5 booster group* includes: six individuals without reported PVIs; three individuals with presumed BA.1 PVIs; four individuals with presumed BA.5 PVIs after three doses of the ancestral COVID-19 vaccine; and three individuals with presumed XBB PVIs after the bivalent booster.…”
Section: Resultssupporting
confidence: 62%
“…Dots indicate results from individual participants, and bars indicate GMT with 95% confidence interval. Neutralization titers against D614G, BA.4/BA.5, BQ.1.1, XBB and XBB.1.5 in the sera of V3+PVI, V4, V3+Bi and V4+Bi were reported previously 29 .…”
Section: Supplemental Informationsupporting
confidence: 55%
See 2 more Smart Citations
“…Comparing neutralization data obtained against the vaccine components and other variants, different reports, including our previous study on PWH, demonstrated decreased response against BQ.1.1 and more importantly against XBB sublineages 16,19–21 …”
Section: Discussionmentioning
confidence: 80%